Using purpose-made objects for visual research: an exploratory case study. (May 2015) - Hinthorne, Lauren Leigh; Simpson Reeves, Laura
This article responds to Pauwels' assertion that visual research is no longer the (nearly) exclusive domain of camera-based visual materials and methods. The authors argue that, in certain contexts, objects can provide appropriate and valid visual research materials in their own right. The article begins by examining the institutionalized parameters for visual research established by this journal ( Visual Communication ), Visual Studies and the International Visual Sociology Association. Next, a careful review of the contemporary literature reveals that objects are already recognized as legitimate visual research materials, albeit discreetly. After describing an exploratory research process that integrated participatory mapping and 3D model-building activities, the authors discuss the potential of purpose-made objects as a distinctive type of visual material. The article concludes by encouraging the acceptance of visual research that looks beyond images.